FEATURES OF ORTHOPEDIC TREATMENT OF PATIENTS WITH DIABETES MELLITUS - Burxonova Zarafruz Qobilovna, Egamov Azizjon Nodirovich (Journals Park Publishing, 2023)
Diabetes mellitus is the most important medical and social problem of modern society. Currently, according to the International Diabetes Federation (IDF), there are 415 million people in the world who have diabetes. [1] According to WHO, the term "diabetes mellitus" means a metabolic disorder of multiple etiologies characterized by chronic hyperglycemia with abnormal carbohydrate, fat, and protein metabolism as a result of impaired insulin secretion and/or insulin action. In this regard, there are two forms of primary diabetes mellitus. Type I - insulin-dependent diabetes mellitus, which is characterized by insufficient insulin synthesis by Langerhans cells. Type II - non-insulin-dependent diabetes mellitus, this disease is associated with chronic hyperglycemia, which develops as a result of a violation of the interaction of insulin with tissue cells (WHO, 1999). [1, 2, p. 786-791] Secondary or symptomatic diabetes mellitus is also distinguished, which is caused by diseases or substances that affect the endocrine apparatus of the pancreas or insulin receptors.
Keywords: diabetes mellitus, orthopedic treatment, oral cavity, intermediate rinse, integrated approach, bone tissue.